Increased Acid Stability of the Hemagglutinin Protein Enhances H5N1 Influenza Virus Growth in the Upper Respiratory Tract but Is Insufficient for Transmission in Ferrets - Zaraket, Hassan (American Society for Microbiology, 2013)
Influenza virus entry is mediated by the acidic-pH-induced activation of hemagglutinin (HA) protein. Here, we investigated how a decrease in the HA activation pH (an increase in acid stability) influences the properties of highly pathogenic H5N1 influenza virus in mammalian hosts. We generated isogenic A/Vietnam/1203/2004 (H5N1) (VN1203) viruses containing either wild-type HA protein (activation pH 6.0) or an HA2-K58I point mutation (K to I at position 58) (activation pH 5.5). The VN1203-HA2-K58I virus had replication kinetics similar to those of wild-type VN1203 in MDCK and normal human bronchial epithelial cells and yet had reduced growth in human alveolar A549 cells, which were found to have a higher endosomal pH than MDCK cells. Wild-type and HA2-K58I viruses promoted similar levels of morbidity and mortality in C57BL/6J mice and ferrets, and neither virus transmitted efficiently to naive contact cage-mate ferrets. The acid-stabilizing HA2-K58I mutation, which diminishes H5N1 replication and transmission in ducks, increased the virus load in the ferret nasal cavity early during infection while simultaneously reducing the virus load in the lungs. Overall, a single, acid-stabilizing mutation was found to enhance the growth of an H5N1 influenza virus in the mammalian upper respiratory tract, and yet it was insufficient to enable contact transmission in ferrets in the absence of additional mutations that confer α(2,6) receptor binding specificity and remove a critical N-linked glycosylation site. The information provided here on the contribution of HA acid stability to H5N1 influenza virus fitness and transmissibility in mammals in the background of a non-laboratory-adapted virus provides essential information for the surveillance and assessment of the pandemic potential of currently circulating H5N1 viruses.